The Influence of Operational Synergy, Cost Efficiency, and Diversification Strategy on the Financial Sustainability of Post-Merger Higher Education Institutions - Sudirman, Sudirman; Ridwan, Ridwan (Sean Institute, 2025)
Many private higher education institutions (PHEIs) in Indonesia are currently struggling with declining student enrollment, limited funding, and accreditation pressures. These systemic challenges call for strategic responses that can ensure institutional viability and sustainability.This study aims to examine the phenomenon of private higher education institution (PHEI) mergers in Indonesia during the period 2020–2024, with a focus on their implications for operational efficiency, institutional governance, and financial sustainability. This issue has gained urgency as a growing number of PHEIs face challenges related to accreditation, declining student enrollment, and limited resources. Mergers are seen as an adaptive strategy to strengthen competitiveness and enhance institutional management. The research adopts a quantitative approach with a descriptive-verificative design. Data were collected through document analysis from national media sources and official data from the Ministry of Education, Culture, Research, and Technology, as well as surveys conducted with leaders of PHEIs that have undergone legal merger processes. Respondents were selected using purposive sampling, based on the primary criterion of having completed a formal merger within the past five years. The findings reveal that mergers positively impact operational efficiency and institutional consolidation, particularly in reducing operational costs, optimizing human resources, and strengthening governance structures. However, the success of a merger is also influenced by organizational culture readiness, alignment of vision and mission between institutions, and policy support from the government. Several challenges identified include internal resistance, complex administrative procedures, and asset distribution disparities post-merger. This research offers valuable insights for policymakers, PHEI administrators, and higher education stakeholders in understanding the dynamics of mergers as a strategic pathway for institutional transformation. Moving forward, more adaptive regulations and intensive government assistance are needed to ensure that merger processes are effective and sustainable.